The meaningfulness of the institution of control for the sustainable development of society - Хмельков, Андрей Владимирович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
In this paper we take an opportunity by the example of largest and most ambitious plan to transform the current conditions of the world approved by the peoples of the United Nations (Resolution of the United Nations General Assembly – “Transforming our world: the 2030 Agenda for Sustainable Development), to determine the value of the institute of control and its agents for the sustainable development of the society, the state, the accumulation and saving public finances, the provision of public goods, i.e. for a positive transformation of the future of our world. By defining the essence of the Agenda for the sustainable development there was determined a competence of the Control Institute with the conclusion that there should be included the goals and objectives of this Agenda that can be brought to effect through the appropriate actions of its agents.  So the definition of the “agent of the Control Institute” was specified by featuring more emphasis on the terminology of national and supranational levels and also, by excluding the role of the Control Institute ensuring stability of public finances. It means eliminating negative variation of the approved parameters of public finances and defining the value of the institute of control “as one of the most essential elements of the social framework”. Consequently, the definition of the “Institute of Control” was specified to improve the institutional infrastructure of public finances. The result of the study was the achievement of the goals and specific objectives.